Increasing Availability of Services for Youth at Risk for Suicide: An Example of a Brief Crisis Intervention Protocol. Issue 3 (3rd July 2021) - Berk, Michele S.; Starace, Nicole; Glasser, Cynthia
ABSTRACT: In this article, we describe the Stanford Crisis Clinic protocol, a brief, evidence-informed clinical service that we developed to address the barriers to care for youth with SITBs in our local community. The Crisis Clinic is housed within the larger general outpatient child and adolescent psychiatry clinic run by the Division of Child and Adolescent Psychiatry and Child Development, in the Department of Psychiatry and Behavioral Sciences at the Stanford University School of Medicine. The general child and adolescent outpatient clinic provides mental health services primarily to residents of Santa Clara and San Mateo Counties in the state of California. Both are large, ethnically and economically diverse counties that are home to Silicon Valley and part of the larger San Francisco Bay Area. The clinic conducts approximately 20, 542 patient visits, receives approximately 3500 new referrals, and sees over 2000 new patients each year across several sub-specialty clinics within the larger general clinic. The clinic is one of the few that accept private insurance in the local area; hence, the demand often exceeds the supply of providers and wait times are typically several months long. The clinic does not currently serve clients with public insurance (i.e., MediCal). For the Crisis Clinic, our goal was to create a time-limited program, consisting of evidence-based safety interventions and best-practice recommendations, in order to treat as many youth with SITBs seeking treatment at Stanford as possible.